Multipliers of Fourier-Haar Series in Lorentz Spaces - Tleukhanova, Nazerke; Bashirova, Anar (Eurasian Mathematical Journal, 2022)
This article provides a complete description of the multipliers of the Fourier series along the Haar system in the Lorentz spaces \(L_p,r\). Necessary and sufficient conditions are obtained ensuring that \({λ_k^j}_k=0,j=1^∞,2^k m(L_p,r → L_q,s)\). This work generalizes and supplements the result of work [8].